Intrauterine synechiae and chronic endometritis - is there a causal relationship? - Mekan R. Orazov; Liudmila M. Mikhaleva; Sevinc Ya. Ismayilzade; Tatiana V. Bezuglova; Elena V. Lagutina (IP Berlin A.V., 2022)
Both in our country and around the world, childless marriages currently remain an important medical and social problem, the frequency of which remains high and has no tendency to decrease. One of the main roles in the structure of this condition is the uterine factor of infertility. In the structure of the uterine factor, a separate place belongs to intrauterine synechiae associated with chronic endometritis. The high prevalence, unclear mechanisms of pathogenesis and the lack of a unified approach to therapy determines not only the relevance of the chosen topic, but also the need for an integrated approach to the management of patients suffering from uterine infertility. The article presents modern ideas about the tactics of treatment of patients with infertility of uterine genesis associated with chronic endometritis and intrauterine synechiae, according to domestic and foreign literature.